Alterations of biaxial viscoelastic properties of the right ventricle in pulmonary hypertension development in rest and acute stress conditions - Liu, Wenqiang; LeBar, Kristen; Roth, Kellan; Pang, Jassia; Ayers, Jessica; Chicco, Adam J.; Puttlitz, Christian M.; Wang, Zhijie (Frontiers in Bioengineering and Biotechnology, 2023)
The right ventricle (RV) mechanical property is an important determinant of its function. However, compared to its elasticity, RV viscoelasticity is much less studied, and it remains unclear how pulmonary hypertension (PH) alters RV viscoelasticity. Our goal was to characterize the changes in RV free wall (RVFW) anisotropic viscoelastic properties with PH development and at varied heart rates. PH was induced in rats by monocrotaline treatment, and the RV function was quantified by echocardiography. After euthanasia, equibiaxial stress relaxation tests were performed on RVFWs from healthy and PH rats at various strain-rates and strain levels, which recapitulate physiological deformations at varied heart rates (at rest and under acute stress) and diastole phases (at early and late filling), respectively. We observed that PH increased RVFW viscoelasticity in both longitudinal (outflow tract) and circumferential directions. The tissue anisotropy was pronounced for the diseased RVs, not healthy RVs. We also examined the relative change of viscosity to elasticity by the damping capacity (ratio of dissipated energy to total energy), and we found that PH decreased RVFW damping capacity in both directions. The RV viscoelasticity was also differently altered from resting to acute stress conditions between the groups – the damping capacity was decreased only in the circumferential direction for healthy RVs, but it was reduced in both directions for diseased RVs. Lastly, we found some correlations between the damping capacity and RV function indices and there was no correlation between elasticity or viscosity and RV function. Thus, the RV damping capacity may be a better indicator of RV function than elasticity or viscosity alone. These novel findings on RV dynamic mechanical properties offer deeper insights into the role of RV biomechanics in the adaptation of RV to chronic pressure overload and acute stress.